Highly Efficient Silicon Nanowire Surface Passivation by Bismuth Nano-Coating for Multifunctional Bi@SiNWs Heterostructures - Mariem Naffeti; Pablo Aitor Postigo; Radhouane Chtourou; Mohamed Ali Zaïbi (Nanomaterials, 2020)
A key requirement for the development of highly efficient silicon nanowires (SiNWs) for use in various kinds of cutting-edge applications is the outstanding passivation of their surfaces. In this vein, we report on a superior passivation of a SiNWs surface by bismuth nano-coating (BiNC) for the first time. A metal-assisted chemical etching technique was used to produce the SiNW arrays, while the BiNCs were anchored on the NWs through thermal evaporation. The systematic studies by Scanning Electron Microscopy (SEM), energy dispersive X-ray spectra (EDX), and Fourier Transform Infra-Red (FTIR) spectroscopies highlight the successful decoration of SiNWs by BiNC. The photoluminescence (PL) emission properties of the samples were studied in the visible and near-infrared (NIR) spectral range. Interestingly, nine-fold visible PL enhancement and NIR broadband emission were recorded for the Bi-modified SiNWs. To our best knowledge, this is the first observation of NIR luminescence from Bi-coated SiNWs (Bi@SiNWs), and thus sheds light on a new family of Bi-doped materials operating in the NIR and covering the important telecommunication wavelengths. Excellent anti-reflectance abilities of ~10% and 8% are observed for pure SiNWs and Bi@SiNWs, respectively, as compared to the Si wafer (50–90%). A large decrease in the recombination activities is also obtained from Bi@SiNWs heterostructures. The reasons behind the superior improvement of the Bi@SiNWs performance are discussed in detail. The findings demonstrate the effectiveness of Bi as a novel surface passivation coating, where Bi@SiNWs heterostructures are very promising and multifunctional for photovoltaics, optoelectronics, and telecommunications.